THE QUALITY OF GROUNDWATER OF KIPTIVSKA RURAL TERRITORIAL COMMUNITY (CHERNIHIV REGION) - Kotelchuk Андрій; Bondar Олена; Savchenko Олеся; Kurmakova Ірина; Kotelchuk Леонід; Rybalochko Олена; Rudenko Аліна (Biota. Human. Technology, 2025)
The paper examines groundwater samples from the Kiptivska rural territorial community in the Chernihiv region. Water samples for the study were collected from eight control points at depths ranging from 26 to 36 meters. The analysis assessed various parameters, including organoleptic characteristics (smell, taste, aftertaste), physicochemical properties (pH, total mineralization, total hardness, total alkalinity, total iron content and concentrations of NH4+, NO3-, Mn2+ ions), as well as microbiological indicators (total microbial count, total coliforms, and E. coli). These water samples were collected in December 2024, and the results were compared to normative values, specifically Hygienic Requirements for Drinking Water Intended for Human Consumption» (DSanPiN 2.2.4-171-10). Purpose of the work: to assess the water quality of groundwater intakes of the Kiptivska rural territorial community of Chernihiv district of Chernihiv region to solve the problem of providing the population with quality drinking water. Methodology. The organoleptic (smell, taste, aftertaste), physicochemical (pH, total mineralization, total hardness, total alkalinity, total iron content, content of NH4+, NO3-, Mn2+ ions) and microbiological (total microbial count, total coliforms, E. coli) indicators of water samples taken from groundwater intakes of the Kiptivska rural territorial community of Chernihiv district, Chernihiv region. Scientific novelty is analyzing the groundwater intakes of the Kiptivska rural territorial community of Chernihiv region. Conclusions: The hydrogen index (pH), mineralization, and total hardness in the groundwater of the Kiptivska territorial community of Chernihiv district are within the normal range. The concentration of total Ferric exceeds the maximum permissible concentration by 1,7-3,8 times and of Manganese ions by 2,4–16,4 times. In order to improve the quality of drinking water supply in the long term, it is recommended to organize water intake from deeper aquifers that are less vulnerable to surface and man-made pollution.